PHILOSOPHICAL UNDERSTANDING OF THE TRANSITIONALITY OF UKRAINIAN SOCIETY UNDER CONDITIONS OF ARMED CONFLICT - Khailak, Denys (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The article examines the phenomenon of transitivity in Ukrainian society in the context of armed conflict. The problem is relevant because war radically intensifies transitional processes, transforming them from a latent state of uncertainty into an active factor of social, cultural, and political change. The aim and tasks. The aim of the study is to analyze the specificity of the transit process in wartime and its influence on the dynamics of social change. The tasks are to clarify the meaning of transitivity in the Ukrainian context, to substantiate the idea that war sharpens the experience of transition, and to show how radical crisis may contribute to social transformation. Research methods. The study is based on a phenomenological approach, particularly the ideas of Maurice Merleau-Ponty, which make it possible to analyze changes in bodily, spatial, and temporal experience under the conditions of war. Hermeneutic methodology, cultural analysis, and socio-philosophical interpretation are also used. Research results. The article argues that war does not simply interrupt Ukrainian transitivity but radicalizes it. Armed conflict destroys previous models of stability, changes everyday perceptions of security and space, and intensifies the need for collective self-determination. Ukrainian culture is interpreted as a means of understanding traumatic experience, articulating resistance, and forming new modes of solidarity and political subjectivity. Discussion. The results are compared with interpretations of war as “interrupted transition” and with theories of post-communist transformation. The Ukrainian case shows that radical historical crisis may accelerate political consolidation, although it does not automatically complete all transit processes. The study also questions deterministic views of Ukraine as a “divided state.” Conclusions. The transitivity of Ukrainian society in wartime should be understood as a contradictory process in which trauma, existential threat, and social mobilization coexist. War deepens crisis phenomena but also creates conditions for rethinking collective identity, strengthening civic solidarity, and affirming political subjectivity.